Озерные страсти: роман / Татьяна Алюшина - Алюшина Татьяна Александровна (Эксмо, 2021)
Экземпляры: абонемент (20210312) / Инвентарный номер: 45774 / Цена: / Авт.знак: А 59 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Руc)6-44